Sharia Stock Selection in Indonesia Stock Exchange (IDX) : A fuzzy-ANP Approach - Ghoni, Muhammad Abdul; Mutiara, Rahma (El-Barka Journal of Islamic Economics and Business, 2022)
The purpose of this study is to develop a fuzzy analytic network process (FANP) model to evaluate and select a portfolio of Islamic stocks on the Indonesia Stock Exchange (IDX). A fuzzy analytic network process (FANP) is used to the develop indicator and portfolio selection ranking. It can make it easier for investors to make investment decisions through financial portfolio return. However, in fact and reality, investors need fast investment decision, therefore, portfolio selection is most important. The fuzzy-ANP analysis method can be used to evaluate and to make prioritize ranking of investment decision variables. The results of this study are found that profitability is the most important criterion for investors to select Islamic stock portfolios in Indonesia stock exchange. In addition, the value of Return on assets (ROA), Return on equity (ROE), Return on Investment (ROI), Net profit margin (NPM), Earning per share, return on sales Ratio and Return on Capital of a company.